ANALISIS KESULITAN SISWA SMA NEGERI 1 KEDUNGWUNI MATERI LOGARITMA - Hayati, Istifada Nurul; Budiyono, Budiyono (Universitas Sebelas Maret, 2018)
Abstract:During the process of mathematics learning, problem solving is one of the important factors in influencing the success of mathematics learning. The objective of this study is determining students’ difficulties in understanding logarithm functions. It is also intended to find out alternative solutions in overcoming the problems. The form of this research is a qualitative descriptive study using Spradley model data analysis through research procedures from Sudjana publication book. Based on preliminary observations, students’ mathematics problem solving skill at SMAN 1 KEDUNGWUNI has various ways. The number of students of class X MIPA 3 SMAN 1 Kedungwuni 1 is 32 students. 25% of students have high problem-solving skill, whereas 75% have low problem-solving skill. The cause of the problem is derived from teachers, students, and learning tools. Students’ mistakes in solving some tasks related to logarithm functions material become obstacles in the next learning process. The written test analysis results and interviews results of students regarding their difficulties in solving logarithm function include: students tend to have low understanding related to initial concepts of logarithm functions, students have difficulty in understanding the application of logarithm functions, and they find a difficulty in applying it into task in the form of story. Alternative solutions that can be implemented to deal with these problems are building the concept of logarithm functions from the previous chapter, namely root and exponent, emphasizing the concept of logarithm functions by giving related tasks, and practicing more tasks about logarithm functions.Keywords:Analysis, Mathematics, Logarithms, Roots, Exponents.